Battery Life Estimation for Embedded System - Prof. V.A.kulkarni; K alekar .Vikram V.; M ore Uday S.; K umbhar Onkar P (International Journal of Innovations in Engineering Research and Technology, 2021)
A battery system consist many battery cells with different characteristics to achievereliable, efficient and extended utilization of battery. The battery managementsystemprovidesindividual level of battery. This level of battery provide information about stateof charge, state of health of the battery. The current battery technology provide modulelevel with voltage sensor.The object of this project to determine and the display thesupply frequency.